Age structure of European ash (Fraxinus excelsior L.) forests in the Left- Bank Forest-Steppe of Ukraine - Meshkova, V. L.; Borysova, V. L. (Forestry and Forest Melioration, 2019)
Introduction European ash (Fraxinus excelsior L.) is currently threatened across most of its distributional range by ash dieback caused by Hymenoscyphus fraxineus. It is also affected by tuberculosis and damaged by insects. All that results in the premature death of trees and stands and deterioration of wood quality. Our previous research showed that susceptibility of European ash to different pathogens as well as the severity of tree damage increase with tree age. In such a case, the maturity age evaluated by growth dynamics is much higher than the actual age of tree mortality caused by a disease. The aim of this work was to define the age structure of European ash stands in the Left-Bank Forest-Steppe considering forest site conditions, stand origin, site index and ash proportion in the forest composition. Materials and Methods The “Ukrderzhlisproekt” Production Association Database (by 2011) was analyzed for the State Forest Enterprises located in the Left-Bank Forest-Steppe. The probability of stand survival up to the mentioned age class was modeled by the method of Demakov. According to the latter, the proportion of the stand area of each 10-year age class was evaluated for each set of subcompartments with respective forest origin, site condition, site index and proportion of European ash in the stand composition. Then the proportion of stands’ area, which survives up to a certain age, was evaluated. Results The average age of ash stands is 68 years for the Left-Bank Forest-Steppe. On average, from 46.1 % to 81.6% of European ash stands survive up to the V age class. The average age of ash stands is the highest in the forest-steppe part of Sumy Region in fresh and moist fertile site types, in Kharkiv Region in dry fertile site type, and in Poltava Region in fresh and moist fairly fertile site types. The average age is the highest (75 years) in artificial seed stands in Kharkiv Region, in stands of natural seed (86 years) and vegetative (77 years) origin in Sumy Region. The survival of pure and almost pure ash stands is the highest in Kharkiv Region and the lowest in Poltava Region. In the legislatively adopted maturity age (VIII age class) the survival of European ash with its proportion of 80–100% in the composition is 26.5 %, 13.1 %, and 3.2 % in Kharkiv, Sumy, and Poltava Regions respectively. Correction of the age of the main felling in forests that are possible for exploitation is suggested considering the possible loss of timber quality as a result of forest damage by different causes. 4 Figs., 9 Tables, 20 Refs.